Flexibility enables to discriminate between ligands: Lessons from structural ensembles of Bcl-xl and Mcl-1. (December 2018) - Maity, Atanu; Majumdar, Sarmistha; Ghosh Dastidar, Shubhra
Graphical abstract: Highlights: Binding pocket of Bcl-xl and Mcl-1 changes conformation differently with ligand. Change in pocket shape upon binding of different type of ligand is higher in Bcl-xl. Binding pocket residues with maximum structural variance have evolved differently. Important binding pocket residues are more conserved in Bcl-xl than those in Mcl-1. Abstract: The proteins of Bcl-2 family, which are promising anti-cancer-drug targets, have substantial similarity in primary sequence and share homologous domains as well as similar structural folds. In spite of similarities in sequence and structures, the members of its pro- and anti- apoptotic subgroups form complexes with different type of partners with discriminating binding affinities. Understanding the origin of this discrimination is very important for designing ligands that can either selectively target a protein or could be made broad ranged as necessary. Using principal component analysis (PCA) of the available structures and from the analysis of the evolution of the binding pocket residues, the correlation has been investigated considering two important anti-apoptotic protein Bcl-xl and Mcl-1, which serve as two ideal representatives of this family. The flexibility of the receptor enables them to discriminate between the ligands or the binding partners. It has been observed that although Bcl-xl and Mcl-1 are classified as homologous proteins, through the course of evolution the binding pocket residues are highly conserved for Bcl-xl; whereas they have been substituted frequently in Mcl-1. The investigation has revealed that the Bcl-xl can adjust the backbone conformation of the binding pocket residues to a larger extent to complement with the shape of different binding partners whereas the Mcl-1 shows more variation in the side chain conformation of binding pocket residues for the same purpose.